2014
DOI: 10.1002/ace.20109
|View full text |Cite
|
Sign up to set email alerts
|

Race, the Black Male, and Heterogeneous Racisms in Education

Abstract: This chapter explores the effects of historical and current racism on the educational experiences of American Black males. The authors use critical race theory to illustrate how assumptions about culture and gender have subverted the egalitarian ideals of adult education. Teachers and students are urged to use critical reflection and open discussion about racial issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Regretfully, what we do know about Black males in America is that they are characterized by society as individuals who are difficult to reach and rarely discussed in adult education literature (Drayton, ). Some scholars have reported that negative school experiences (Drayton, ) have resulted in the high school dropout rates of Black males higher and college entry rates lower than any other culture (Johnson‐Bailey, Ray, & Lasker‐Scott, ). As a result, their voices are silenced (Drayton, Rosser‐Mims, Schwartz, & Guy, ) leading to further misunderstandings of Black males “nuanced in dimensions and interconnections of racism, gender, and citizenship” (p. 97).…”
Section: Comin’ Up Shortmentioning
confidence: 99%
See 2 more Smart Citations
“…Regretfully, what we do know about Black males in America is that they are characterized by society as individuals who are difficult to reach and rarely discussed in adult education literature (Drayton, ). Some scholars have reported that negative school experiences (Drayton, ) have resulted in the high school dropout rates of Black males higher and college entry rates lower than any other culture (Johnson‐Bailey, Ray, & Lasker‐Scott, ). As a result, their voices are silenced (Drayton, Rosser‐Mims, Schwartz, & Guy, ) leading to further misunderstandings of Black males “nuanced in dimensions and interconnections of racism, gender, and citizenship” (p. 97).…”
Section: Comin’ Up Shortmentioning
confidence: 99%
“…Racial hierarchies determine who gets tangible benefits, including the best jobs, the best schools, and invitations to parties in people's homes” (Delgado and Stefancic, p. 21). Therefore, racism not only attacks people of color, in this case Black males, it also systematically impedes their access to privileges such as quality education and ultimately affects success in various academic environments (Johnson‐Bailey, Ray, & Lasker‐Scott, ). With oppressive and racist systems in place, Black men are then expected to maintain white male dominated perceptions of a good provider (Drayton, ), a perception that has been met with oppression, denigration, and violence.…”
Section: Comin’ Up Shortmentioning
confidence: 99%
See 1 more Smart Citation
“…The conceptualization of Black manhood, critical race theory, and career development theory provided the framework for the study. The broad assumption that Black men are able to trade on their gender to gain privilege is misleading (Johnson-Bailey, Ray, & Lasker-Scott, 2014). Black men were characterized as intellectually inferior and hypersexual, viewed with contempt, and thought to be incapable of being equal to White men because they were perceived to be racially inferior (Bederman, 1996;hooks, 2000;Hutchinson, 2002;Stewart, 2007).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In this modern day, Black men are still subjects of negative stereotypes that have a lingering impact on the perceptions others hold of them and ramifications for their career development (Holzer & Offner, 2001;Moss & Tilly, 1996. The broad assumption that Black men are able to trade on their gender to gain privilege is misleading (Johnson-Bailey, Ray, & Lasker-Scott, 2014). In reality, the interlocking positional characteristics of race and gender have a cumulative effect of describing a man' s hierarchical standing and New Directions for Adult and Continuing Education • DOI: 10.1002/ace experiences in America; and because of their social position as "Blackmen," being both Black and men, they more often encounter gendered racism (Mutua, 2006).…”
Section: Theoretical Frameworkmentioning
confidence: 99%